Enoxaparin thromboprophylaxis during pregnancy: a review of pharmacist-led interventions - Abdulridha, Ghaith Mohammed; Salah, Ihsan (Pharmakeftiki, 2025)
Enoxaparin, a low-molecular-weight heparin, is a critical agent for anticoagulation during pregnancy due to its efficacy and safety. It is generally used as a prophylactic agent against venous thromboembolism; a particularly serious and dangerous situation when occurring during pregnancy. However, the enoxaparin administration during pregnancy requires accurate dosing and monitoring. Complications as a result of prescribing mistakes highlight the need for competitive control strategies. This review attempts to examine the effects of selected pharmacist-led interventions on enoxaparin-induced thromboprophylaxis in pregnant patients. Based on the findings of studies from the literature, we herein emphasize the crucial role of pharmacists in improving anticoagulation treatment goals, correcting dosing errors, ensuring patient adherence, and protecting from the development of adverse events during antenatal thromboprophylaxis.